2019
DOI: 10.3389/fncel.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Oligomers Increase ER-Mitochondria Ca2+ Cross Talk in Young Hippocampal Neurons and Exacerbate Aging-Induced Intracellular Ca2+ Remodeling

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disorder and strongly associated to aging. AD has been related to excess of neurotoxic oligomers of amyloid β peptide (Aβo), loss of intracellular Ca2+ homeostasis and mitochondrial damage. However, the intimate mechanisms underlying the pathology remain obscure. We have reported recently that long-term cultures of rat hippocampal neurons resembling aging neurons are prone to damage induced by Aβ oligomers (Aβo) while short-term cultured cells resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 75 publications
8
68
0
Order By: Relevance
“…These oscillations can be abolished by tetrodotoxin, indicating they are dependent on synaptic network communication among neurons. However, after several weeks in vitro, the neuronal cultures lose this ability and show increased resting levels of intracellular Ca 2+ concentration relative to the short-term cultures instead [38]. Chronic exposure of rat hippocampal neurons to Aβo for 24 h has no effect on synchronic cytosolic Ca 2+ oscillations.…”
Section: Remodeling Of Intracellular Ca 2+ and Store-operated Ca 2+ Ementioning
confidence: 92%
See 1 more Smart Citation
“…These oscillations can be abolished by tetrodotoxin, indicating they are dependent on synaptic network communication among neurons. However, after several weeks in vitro, the neuronal cultures lose this ability and show increased resting levels of intracellular Ca 2+ concentration relative to the short-term cultures instead [38]. Chronic exposure of rat hippocampal neurons to Aβo for 24 h has no effect on synchronic cytosolic Ca 2+ oscillations.…”
Section: Remodeling Of Intracellular Ca 2+ and Store-operated Ca 2+ Ementioning
confidence: 92%
“…Chronic exposure of rat hippocampal neurons to Aβo for 24 h has no effect on synchronic cytosolic Ca 2+ oscillations. Intriguingly, in aged neurons, Aβo treatment resumes synchronic oscillations [38]. Ca 2+ hyperactivity has also been shown in in vivo mouse models of cerebral amyloidosis [39].…”
Section: Remodeling Of Intracellular Ca 2+ and Store-operated Ca 2+ Ementioning
confidence: 98%
“…Abramov et al (2004a) identified that Aβ causes Ca 2+ -dependent oxidative stress by the activation of NADPH oxidase in astrocytes and that the reduced antioxidant activity induces neuronal death. Recently, Calvo-Rodriguez et al (2019) suggested that Aβ oligomers exacerbate Ca 2+ remodeling from ER to mitochondria in aged neurons but not in young neurons. Conversely, Itkin et al (2011) argued that Ca 2+ stimulates the formation of Aβ oligomers, leading to neuronal toxicity in AD.…”
Section: The Critical Role Of Ca 2+ In the Pathogenesis Of Neurodegenmentioning
confidence: 99%
“…It is tempting to speculate that the same mitoCa 2+ changes we observed in isolated neurons occur in vivo, and might contribute to the synergistic worsening of learning and memory in Drp1KO-hAPP mice. Indeed, mutations in APP and other proteins implicated in AD have been shown to disrupt cytosolic and ER calcium homeostasis (62)(63)(64), and Aß oligomers can increase mitoCa 2+ levels, perhaps due to increased uptake secondary to increased expression of the mitoCa 2+ uniporter (MCU) (65,66). Interestingly, patients with AD have decreased expression of the mitochondrial Na + /Ca 2+ exchanger (NCLX).…”
Section: Therapeutic Potential Of Decreasing Mitoca 2+ and Drp1 In Admentioning
confidence: 99%